Rate of Convergence in Sobolev Space (European Journal of Pure and Applied Mathematics, 2012)
In this paper, a new theorem on degree of approximation inÂ L2 p() Sobolev space of integrable functions of two variables by Bernstein-Chlodowsky polnomials on an unbounded triangular domain is studied. Also by using the K- functional of Peetre the order of approximation are established.